Low-Carbon Economy – A New Challenge for Rural Communes - Gradziuk, Piotr; Gradziuk, Barbara (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2016)
Abstract: The Authors present the results of research into the planned measures to reduce CO2 emissions by local communes. The research was conducted in 2015 in 12 rural communes located in Lubelskie voivodship, which have developed Low-Carbon Econo myPlans (LCEPs). According to the research, CO2 emissions (47%) in the analyzed communes came mainly from the consumption of liquid fuels in transport (mainly transit) as well as by tractors and self-propelled agricultural machinery. The remaining causes of the emissions (53%) included the use of fossil fuels such as coal (31%), natural gas and heating oil (2% as well as electricity (20%) generated outside the area of the communes concerned. Among many various possibilities for reducing CO2 emissions identified in LCEPs the most important will be the substitution of conventional energy sources with renewable ones, including mainly biomass and solar energy.
Keywords: low-carbon economy plan; low-carbon economy; rural communes; greenhouse gases; renewable energy sources